# trigoo

(sinx-cosx)^2=sin2x

1. 👍 0
2. 👎 0
3. 👁 98
1. What are we doing? Solving?

of so, then square both sides

sin^2 - 2sinxcosx + cos^2 = sin2x
1 - sin2x = sin2x
2sin2x = 1
sin2x = 1/2
2x = 30° or 150°
x = 15° or 75°

since we squared, all answers must be checked ..
if x=15°
LS = (sin15 - cos15)^2 = .5
RS = sin 30 = .5 = Ls, so x=15° works

if x = 75°
Ls = (sin75-cos75)^2 = .5
RS = sin 150 = .5 , so x = 75° works

x = π/12 and 5π/12

1. 👍 0
2. 👎 0
posted by Reiny
2. thnx thnx so much

1. 👍 0
2. 👎 0
posted by Dexi

## Similar Questions

1. ### Trig........

I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top

asked by abdo on April 18, 2007
2. ### Calculus - Integration

I ran across this one the other day. See what you can make of it. Find the integral of ecosxsinx - (sinx+cosx)esinx+cosx ----------------------------------------- esin2x-2esinx+1

asked by oobleck on May 22, 2019
3. ### Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

asked by Ashley on April 14, 2007
4. ### Math 12

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.

asked by Anonymous on February 20, 2012
5. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.

asked by Anonymous on February 20, 2012
6. ### Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] =

asked by Anonymous on February 20, 2012
7. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 -

asked by Dave on January 2, 2007
8. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated

asked by mo on April 18, 2007
9. ### check math

Here are my answers. Can you check if I got the right answers? Thank you! (x+3)(x-3)>0 answer: x3 x^2-2x-15

asked by Anonymous on August 8, 2007
10. ### trigonometry

can i use factoring to simplify this trig identity? the problem is sinx + cotx * cosx i know the answer is cscx and i know how to get it but i want to know if i can do factoring to get it bc i tried to but it wont give me the

asked by v on December 3, 2012
11. ### maths - trigonometry

I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the

asked by anonymous on June 19, 2010

More Similar Questions